INCREASING THE STUDENTS’ VOCABULARY ACHIEVEMENT IN WRITING SKILL THROUGH WORD ANALOGY TECHNIQUE - Alamsari; Ampa, Hj. Andi Tenri; Natsir, Ratu Yulianti (English Language Teaching Methodology, 2024)
The objectives of this research is to find out How are the students’ vocabularies achievement in Writing through word analogy technique in term of noun at the Seventh Grade of MTS Al-hidayah Lemoa and How are the students’ vocabularies achievement through word analogy technique in term of adjective at the Seventh Grade of MTS Al Hidayah Lemoa. This research used Classroom Action Research (CAR), which consists of two cycles and each cycle has four meetings. The result of the study was the used of Word Analogy Tecnique in teaching vocabulary substantially increased students’ vocabulary achievement at MTS Al Hidayah Lemoa. The students increased in vocabulary after using word analogy technique was very good. The students total score in nouns got 895 score in cycle I and in cycle II got 1410 score while the students total score in adjective got 900 in cycle I and in cycle II got 1720 score. The mean score for noun in cycle I got 4,5 score and in cycle II got 7,5 score while for adjective in cycle I got 4,5 mean score and in cycle II got 7,8 mean score it shows that from the diagnostic test who noun got 2,9 score and adjective 2,0 score the students’ vocabulary has increased.